Does Oil Rich in Alpha-Linolenic Fatty Acid Cause the Same Immune Modulation as Fish Oil in Walker 256 Tumor-Bearing Rats?. (16th November 2016) - Schiessel, Dalton Luiz; Yamazaki, Ricardo K.; Kryczyk, Marcelo; Coelho de Castro, Isabela; Yamaguchi, Adriana A.; Pequito, Danielle C. T.; Brito, Gleisson A. P.; Borghetti, Gina; Aikawa, Júlia; Nunes, Everson A.; Naliwaiko, Kátia; Fernandes, Luiz C.
ABSTRACT: Objective : Polyunsaturated fatty acids n-3 (PUFA n-3) have shown effects in reducing tumor growth, in particular eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) abundantly present in fish oil (FO). When these fatty acids are provided in the diet, they alter the functions of the cells, particularly in tumor and immune cells. However, the effects of α-linolenic fatty acid (ALA), which is the precursor of EPA and DHA, are controversial. Thus, our objective was to test the effect of this parental fatty acid. Methods : Non-tumor-bearing and tumor-bearing Wistar rats (70 days) were supplemented with 1 g/kg body weight of FO or Oro Inca® (OI) oil (rich in ALA). Immune cells function, proliferation, cytokine production, and subpopulation profile were evaluated. Results : We have shown that innate immune cells enhanced phagocytosis capacity, and increased processing and elimination of antigens. Moreover, there was a decrease in production of pro-inflammatory cytokines (tumor necrosis factor-alpha (TNF-α) and interleukin 6 (IL-6)) by macrophages. Lymphocytes showed decreased proliferation capacity, increased cluster of differentiation 8 (CD8 + ) subpopulation, and increased TNF-α production. Conclusions : Oil rich in ALA caused similar immune modulation in cancer when compared with FO.